Efficacy of Psychological Intervention for Children with Concurrent Posttraumatic Stress Disorder and Mild Traumatic Brain Injury. Issue 3 (11th April 2020) - Shorer, Maayan; Segev, Shira; Rassovsky, Yuri; Fennig, Silvana; Apter, Alan; Peleg, Tammy Pilowsky
Abstract: Posttraumatic stress disorder (PTSD) and mild traumatic brain injury (mTBI) are common conditions following motor vehicle accidents (MVAs). Mild TBI and PTSD not only share similar features but may also coexist and interact. Nonetheless, research on psychotherapeutic interventions for PTSD in patients with a history of mTBI, particularly regarding pediatric populations, is limited. The present study compared the efficacy of the prolonged exposure treatment protocol for children and adolescents (PE‐A) with PTSD and mTBI ( n = 16) versus PTSD alone ( n = 21); treatment commenced at least 3 months following an MVA. Emotional status and cognitive functioning were assessed pre‐ and postintervention using questionnaires and standardized neuropsychological tests. Participants from both groups benefitted from the intervention, as reflected in their emotional status via increased ratings of well‐being and decreased ratings of PTSD, anxiety, depression, and postconcussive symptoms, η 2 = .21–.50. Ratings of cognitive function also improved for cognitive flexibility, η 2 = .30; executive function in everyday life, η 2 = .27; and attention and inhibition, η 2 = .16. Parental PTSD was the strongest predictor of improvement after intervention, sr 2 = .35. Thus, it appears that PE‐A is an effective intervention for children with MVA‐related PTSD regardless of its comorbidity with mTBI. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Eficacia de la Intervención Psicológica en Niños con Trastorno de Estrés Postraumático y Lesión Cerebral Traumática Leve Concurrente. EFICACIA DE LA INTERVENCION EN NIÑOS CON TEPT Y MTBI El trastorno de estrés postraumático (TEPT) y la lesión cerebral traumática leve (mTBI en su sigla en inglés) son afecciones comunes tras accidentes automovilísticos (MVAs en su sigla en inglés). El TEPT y la TBI leve no solo comparten características similares, sino que también pueden coexistir e interactuar. No obstante, la investigación en intervenciones psicoterapéuticas para TEPT en pacientes con antecedentes de mTBI, particularmente en relación a la población pediátrica es limitada. El presente estudio comparó la eficacia del protocolo de tratamiento de exposición prolongada en niños y adolescentes (PE‐A en su sigla en inglés) con TEPT y mTBI ( n = 16) frente a TEPT solo ( n = 21); el tratamiento inició al menos 3 meses después del MVA. El estado emocional y el funcionamiento cognitivo fueron evaluados antes y después de la intervención utilizando cuestionarios y pruebas neuropsicológicas estandarizadas. Los participantes de ambos grupos se beneficiaron de la intervención, como se refleja en su estado emocional a través del incremento en las puntuaciones de bienestar y la disminución en las puntuaciones de TEPT, ansiedad, depresión y síntomas postconcusivos η 2 = .21–.50. Las calificaciones de la función cognitiva también mejoraron para la flexibilidad cognitiva, η 2 = .30; la función ejecutiva en la vida diaria, η 2 = .27; y la atención e inhibición, η 2 = .16. El TEPT en los padres fue el predictor más fuerte de mejoría después de la intervención, sr 2 = .35. Por lo tanto, parece que el protocolo PE‐A es una intervención efectiva para niños con TEPT relacionado a MVA, independientemente de la comorbilidad con la mTBI. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Efficacy of Psychological Intervention for Children with Concurrent Posttraumatic Stress Disorder and Mild Traumatic Brain Injury Traditional Chinese 標題: 對有創傷後壓力症和輕微創傷性腦損傷共病的兒童提供心理干預的功效 撮要: 創傷後壓力症(PTSD)和輕微創傷性腦損傷(mTBI), 乃經歷車禍後的普遍情況。mTBI跟PTSD不但有相似的特徵, 更可同時發生並有相互作用。可是, 目前為止, 對於曾有mTBI的PTSD患者 (特別是兒科患者) 作心理治療干預的研究仍然不足。本研究比較為兒童及青少年而設的延長暴露療法(PE‐A)對患有PTSD和mTBI的樣本(n = 16)及只有PTSD的樣本 (n = 21)的功效。治療在樣本經歷一次MVA後至少三個月才開始進行。我們在干預前後, 以問卷和標準化神經心理測驗, 評估樣本的情緒狀態和認知功能。兩組樣本接受干預後, 情況都有改善:在情緒狀態方面, 幸福感評分提升, 而PTSD、焦慮、抑鬱、腦震盪後症狀評分亦減低 (η 2 = .21–.50) ;在認知方面, 認知彈性 (η 2 = .30) 、日常的執行功能 (η 2 = .27) 、注意力和抑制 (η 2 = .16) 方面的分數亦提升。家長的PTSD情況, 乃樣本接受干預後症狀改善的最強預測變量 (sr 2 = .35) 。因此, PEA對有MVA相關的PTSD兒童來說, 無論有沒有mTBI共病也好, 似乎都是有效的干預。 Simplified Chinese 标题: 对有创伤后压力症和轻微创伤性脑损伤共病的儿童提供心理干预的功效 撮要: 创伤后压力症(PTSD)和轻微创伤性脑损伤(mTBI), 乃经历车祸后的普遍情况。mTBI跟PTSD不但有相似的特征, 更可同时发生并有相互作用。可是, 目前为止, 对于曾有mTBI的PTSD患者 (特别是儿科患者) 作心理治疗干预的研究仍然不足。本研究比较为儿童及青少年而设的延长暴露疗法(PE‐A)对患有PTSD和mTBI的样本(n = 16)及只有PTSD的样本 (n = 21)的功效。治疗在样本经历一次MVA后至少三个月才开始进行。我们在干预前后, 以问卷和标准化神经心理测验, 评估样本的情绪状态和认知功能。两组样本接受干预后, 情况都有改善:在情绪状态方面, 幸福感评分提升, 而PTSD、焦虑、抑郁、脑震荡后症状评分亦减低 (η 2 = .21–.50) ;在认知方面, 认知弹性 (η 2 = .30) 、日常的执行功能 (η 2 = .27) 、注意力和抑制 (η 2 = .16) 方面的分数亦提升。家长的PTSD情况, 乃样本接受干预后症状改善的最强预测变量 (sr 2 = .35) 。因此, PEA对有MVA相关的PTSD儿童来说, 无论有没有mTBI共病也好, 似乎都是有效的干预。